Experimental description of strength and tribological characteristic of EFB oil palm fibres/epoxy composites with technologically undemanding preparation. (1st August 2017) - Valášek, Petr; Ruggiero, Alessandro; Müller, Miroslav
Abstract: Natural materials as fillers of polymers are of increasing potential in modern industrial branches. Their price as well as very good mechanical properties speaks for their use. The industrial application of natural fillers is also predetermined by economic aspects and a relationship to the environment - a prioritization of renewable resources when it is necessary to find adequate utilization for secondary materials coming into being e.g. in case of processing commodities of an oil palm - a palm oil. The paper describes basic strength characteristics of a short-fibre chaotic system with fibres gained from the waste - empty fruit bunches (EFB) - come into being during the process of the oil pressing. The experimental approach of this paper describes undemanding preparation of composite systems without using special technologies with a respect to needs of developing countries and simple applications above all. The experimental program compares the composite systems with non-treated fibres with the system with chemically treated surface of the fibres by 6% solution of NaOH. An electron microscopy was used for an evaluation of an interfacial interaction. The experiment describes short-fibre composites, studies the influence of the length (3, 6 and 9 mm) and the influence of the fibre concentration (2.5–10.0 vol %) on observed characteristics - tensile strength, module of elasticity, hardness and two-body abrasion. The chemical treatment of the fibre surface by the solution of NaOH influenced the surface structure of the fibres and it optimized the interaction of the fibres with used matrix. The inclusion of short EFB fibres increased the modulus of elasticity up of 47% and it decreased the tensile strength of 26%. EFB fibres did not significantly decrease an ability of the material to resist to the two-body abrasion. Described composite system and a production process can be marked as a sustainable manufacturing.